Improved biomonitoring of airborne contaminants by combined use of holm oak leaves and epiphytic moss - De Nicola, F.; Spagnuolo, V.; Baldantoni, D.; Sessa, L.; Alfani, A.; Bargagli, R.; Monaci, F.; Terracciano, S.; Giordano, S. (CHEMOSPHERE, 2013)
Concentrations of 12 elements (Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn) and 16 EPA-listed PAHs were detected in Quercus ilex leaves and the epiphytic moss Leptodon smithii collected at urban, periurban and extraurban holm oak stands, in two Italian Regions (Campania and Tuscany). Levels of environmental contaminants were generally higher in leaves and moss from urban areas than periurban and extraurban ones and samples from Campania had the highest PAH content. The epiphytic moss accumulated higher concentrations of trace elements than leaves and the latter showed a higher accumulation capability for PAHs, especially for those with low molecular weight. The different bioaccumulation in leaves and moss were explained in terms of their distinctive morphological and ecophysiological characteristics. The combined approach seems a promising tool for the monitoring of a wide range of pollutants in Mediterranean urban and extraurban environments. (C) 2013 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Air pollution gradient; Bioaccumulation; Leptodon smithii; PAHs; Quercus ilex; Trace Elements

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis